P2Y12 Platelet Function Assay for Assessment of Bleeding Risk in Coronary Artery Bypass Grafting. Issue 3 (2nd March 2014) - Yu, Pey‐Jen; Cassiere, Hugh A.; Dellis, Sophia L.; Manetta, Frank; Stein, Joanna; Hartman, Alan R.
Abstract Background The use of platelet function testing has been advocated to individualize the time needed between discontinuation of P2Y12 inhibitors and coronary artery bypass grafting (CABG). However, the use of specific point‐of‐care assays to predict bleeding risk in patients on P2Y12 inhibitors prior to CABG has not been fully validated. Methods From September 2012 to May 2013, 81 patients on P2Y12 inhibitors underwent isolated CABG. Preoperative level of P2Y12 receptor blockade was measured using the VerifyNow P2Y12 assay. Packed red blood cell (pRBC) and platelet transfusions and postoperative chest tube output were correlated with preoperative P2Y12 reaction units (PRUs). Results Patients who stopped P2Y12 inhibitors for ≤3 days received significantly more platelet transfusions as compared to those whose inhibitors were stopped for longer (0.71 ± 1.05 units vs. 0.20 ± 0.71 units, p = 0.01). They also had increased postoperative chest tube output (552.5 ± 325.5 mL vs. 399.8 ± 146.5 mL, p = 0.03). There was no significant difference in platelet transfusions and chest tube output between patients whose preoperative PRU value was <250 compared to those whose values were ≥250. pRBC requirements were correlated with preoperative hematocrit and age but not with timing of discontinuation of P2Y12 inhibitors or with PRU levels. Conclusions In patients on P2Y12 inhibitors undergoing CABG surgery, discontinuation of P2Y12 inhibitors three days prior to surgery rather than VerifyNow PRU values predicts postoperative bleeding and the need for platelet transfusions. Sole reliance on platelet function testing to determine the timing of surgery for patients on P2Y12 inhibitors should therefore be done with caution. doi: 10.1111/jocs.12312 (J Card Surg 2014;29:312–316)